2009
DOI: 10.1590/s1806-37132009000200012
|View full text |Cite
|
Sign up to set email alerts
|

Hipertensão arterial pulmonar e doenças da tireoide

Abstract: Recent studies have suggested an association between pulmonary arterial hypertension (PAH) and thyroid diseases (hypothyroidism and hyperthyroidism). This combination has a good prognosis, because the increase in the pulmonary artery pressure is usually slight and reverses after the treatment of the thyroid disease. Although the exact mechanism involved in the pathogenesis of this combination has not yet been established, it has been hypothesized that thyroid hormones and autoimmunity have a direct influence. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Thyroid disorders are classified as mechanisms for the development of Group 5 PH 8 ; however, thyroid disease is also commonly observed concomitantly in patients with PAH (either present during the initial assessments or developing during the course of PAH) 10 , 58 . In both hypothyroidism and hyperthyroidism, cardiac output and pulmonary vascular resistance (PVR) are increased, which in turn can act as a driver for PH 59 , 60 .…”
Section: Management Considerations With Comorbidities and Pulmonary Amentioning
confidence: 99%
“…Thyroid disorders are classified as mechanisms for the development of Group 5 PH 8 ; however, thyroid disease is also commonly observed concomitantly in patients with PAH (either present during the initial assessments or developing during the course of PAH) 10 , 58 . In both hypothyroidism and hyperthyroidism, cardiac output and pulmonary vascular resistance (PVR) are increased, which in turn can act as a driver for PH 59 , 60 .…”
Section: Management Considerations With Comorbidities and Pulmonary Amentioning
confidence: 99%
“…Intraventricular conduction delay in the form of right bundle branch block is present in around 15% of patients, and atrioventricular block may also occur due to unknown reasons. Increased dispersion of QT interval corrected by the heart rate (QTcD) and pulmonary hypertension may also be observed, but their mechanisms are not clear; the same cardiac and hemodynamic changes together with autoimmunity in Graves’ patients may have a role [ 67 , 68 ]. Hyperthyroidism is associated with shortened action potential and increased expression of L-type calcium channel 1D, enhances Na and K permeability, and affects Na pump density [ 69 ].…”
Section: Overt Hyperthyroidismmentioning
confidence: 99%
“…In fact, evidence for such an association exists. Thus, thyroid dysfunctions are for example associated with pulmonary hypertension [ 13 ]. It has also been demonstrated that hyperthyroidism is accompanied by a reduced muscle strength resulting in impaired ventilation under exercise [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%